United European Gastroenterology evidence-based guidelines for the diagnosis and therapy of chronic pancreatitis (HaPanEU). Issue 2 (March 2017) - Löhr, J Matthias; Dominguez-Munoz, Enrique; Rosendahl, Jonas; Besselink, Marc; Mayerle, Julia; Lerch, Markus M; Haas, Stephan; Akisik, Fatih; Kartalis, Nikolaos; Iglesias-Garcia, Julio; Keller, Jutta; Boermeester, Marja; et al.
Background: There have been substantial improvements in the management of chronic pancreatitis, leading to the publication of several national guidelines during recent years. In collaboration with United European Gastroenterology, the working group on 'Harmonizing diagnosis and treatment of chronic pancreatitis across Europe' (HaPanEU) developed these European guidelines using an evidence-based approach. Methods: Twelve multidisciplinary review groups performed systematic literature reviews to answer 101 predefined clinical questions. Recommendations were graded using the Grading of Recommendations Assessment, Development and Evaluation system and the answers were assessed by the entire group in a Delphi process online. The review groups presented their recommendations during the 2015 annual meeting of United European Gastroenterology. At this one-day, interactive conference, relevant remarks were voiced and overall agreement on each recommendation was quantified using plenary voting (Test and Evaluation Directorate). After a final round of adjustments based on these comments, a draft version was sent out to external reviewers. Results: The 101 recommendations covered 12 topics related to the clinical management of chronic pancreatitis: aetiology (working party (WP)1), diagnosis of chronic pancreatitis with imaging (WP2 and WP3), diagnosis of pancreatic exocrine insufficiency (WP4), surgery in chronic pancreatitis (WP5), medical therapy (WP6), endoscopic therapy (WP7), treatment of pancreatic pseudocysts (WP8), pancreatic pain (WP9), nutrition and malnutrition (WP10), diabetes mellitus (WP11) and the natural course of the disease and quality of life (WP12). Using the Grading of Recommendations Assessment, Development and Evaluation system, 70 of the 101 (70%) recommendations were rated as 'strong' and plenary voting revealed 'strong agreement' for 99 (98%) recommendations. Conclusions: The 2016 HaPanEU/United European Gastroenterology guidelines provide evidence-based recommendations concerning key aspects of the medical and surgical management of chronic pancreatitis based on current available evidence. These recommendations should serve as a reference standard for existing management of the disease and as a guide for future clinical research.